A simple load sensor based on a bent single-mode-multimode-single-mode fiber structure - Zulkifli, Ahmad Zarif; Masnan, S.E.F.; Azmi, N.M.; Akib, S.M.; Arof, Hamzah; Harun, Sulaiman Wadi (Elsevier, 2016)
A load sensor is demonstrated using a single-mode-multimode-single-mode (SMS) fiber structure, which is sandwiched between two CR-39 plastic polymer plates. A larger effective transverse strain can be achieved when the distance, D2, between the stage and the edge of the multimode fiber is larger. A higher sensitivity is obtained when D2 = 7 cm with a value of −0.0102 nm/mN, as compared to −0.0027 nm/mN when D2 = 3 cm. In contrast, an FBG integrated in a similar manner has shown an indiscernible change in the wavelength shift as compared to that produced by the SMS device. The result indicates that the proposed SMS device is suitable for sensing a small load or transverse strain with a reasonably high sensitivity.